2017
DOI: 10.2196/jmir.7071
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Facebook in Recruiting Participants for Health Research Purposes: A Systematic Review

Abstract: BackgroundSocial media is a popular online tool that allows users to communicate and exchange information. It allows digital content such as pictures, videos and websites to be shared, discussed, republished and endorsed by its users, their friends and businesses. Adverts can be posted and promoted to specific target audiences by demographics such as region, age or gender. Recruiting for health research is complex with strict requirement criteria imposed on the participants. Traditional research recruitment re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
542
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 648 publications
(624 citation statements)
references
References 40 publications
39
542
3
4
Order By: Relevance
“…Though our click-through rate was similar to prior studies, our response rate was very high, which may have reflected ease of participation in this online survey. Average cost per participant was less than $20, and our best-performing ads were dramatically cheaper, approximately $5-6 per survey participant, a figure that compares very favorably with most prior studies [23,42]. Facebook ads were further disseminated through social sharing, as is illustrated by the 'likes', comments, and sharing of ads that we observed.…”
Section: Key Findingssupporting
confidence: 66%
“…Though our click-through rate was similar to prior studies, our response rate was very high, which may have reflected ease of participation in this online survey. Average cost per participant was less than $20, and our best-performing ads were dramatically cheaper, approximately $5-6 per survey participant, a figure that compares very favorably with most prior studies [23,42]. Facebook ads were further disseminated through social sharing, as is illustrated by the 'likes', comments, and sharing of ads that we observed.…”
Section: Key Findingssupporting
confidence: 66%
“…Most samples were broadly representative, although more Caucasian, highly educated, younger, females were found in some samples 7. This problem is however also common to studies using consecutive recruitment.…”
Section: Self‐referral Recruitmentmentioning
confidence: 99%
“…Studies found Facebook to provide a highly representative sample for young adults and of the general population, with the exception of over sampling young white women [15,16]. In this study, recruitment through Facebook provided a diverse sample, but variation in participant demographics were descriptively different across the Modifications in the enrollment process.…”
Section: Discussionmentioning
confidence: 82%
“…Prior studies have investigated the impact of recruiting participants through various social-media platforms [15] and specifically Facebook [16]. Studies found Facebook to provide a highly representative sample for young adults and of the general population, with the exception of over sampling young white women [15,16].…”
Section: Discussionmentioning
confidence: 99%